Reliability, risk management, and contingency of construction processes and projects - Turskis, Zenonas; Gajzler, Marcin; Dziadosz, Agnieszka (Journal of Civil Engineering and Management, 2012)
The paper presents the evolution of concepts, an overview of research and applications pertaining to reliability in construction production, the use of reserves, robust itineraries, and contingency of time and cost. It describes areas of management advisory systems in relation to the cycle of risk analysis. The article also presents the main trends in different approaches to risk management in construction and construction project processes, such as reliability of production, discount methods, methods of reporting, integrated management together with trends towards standardisation of the investment process management. The discussion is embedded in the specific context: the achievements of trilateral academic colloquia, with participation of Lithuania, Germany and Poland, and a review of work by Professor Kapliński, the chair of the Polish delegation to the aforementioned colloquia. Statybos procesų ir projektų patikimumas, rizikos ir atsitiktinumų valdymas Santrauka. Straipsnyje pateikiama koncepcijų raida, mokslinių tyrimų ir taikomųjų programų, susijusių su statybos produkcijos pati-kimumu, atsargų, patikimų maršrutų bei laiko ir lėšų naudojimo nenumatytais atvejais, apžvalga. Aprašomos valdymo konsultavimo sistemų sritys, atsižvelgiant į rizikos analizės ciklą. Straipsnyje taip pat apžvelgiamos pagrindinės skirtingų požiūrių į rizikos valdymą statybos ir statybos projektavimo procesų metu tendencijos, pavyzdžiui, gamybos patikimumo, diskonto metodai, atskaitomybės metodai, integruotas valdymas bei investicinio proceso valdymo standartizavimo ten-dencijos. Diskusija pateikiama specifiniame trišalio akademinio bendradarbiavimo, dalyvaujant Lietuvai, Vokietijai ir Lenkijai, bei Lenkijos delegacijos pirmininko profesoriaus Kapliński pasiekimų kontekste. Reikšminiai žodžiai: statybos procesai, statybos projektai, patikimumas, rizikos valdymas, apžvalga.